The politics of heritage education: an analysis of national curriculum guidelines in Estonia, Finland, and Sweden - Immonen, Visa; Sivula, Anna (Informa UK Limited, 2025)
Heritage education is present in many educational institutions and their study programmes but not often directly addressed in national curriculum guidelines. The guideline documents of Estonia, Finland, and Sweden for compulsory basic education (children from 7 to 16 years old) are a case in point, and this article analyses how heritage is defined, in which contexts it appears, and what kind of effects it has in these educational policies. To accomplish this analysis, Critical Discourse Analysis is employed as a conceptual framework. It is argued that despite the claim made in the policies regarding heritage belonging to all, heritage is placed in opposition to history writing and associated with minority groups.Heritage education is present in many educational institutions and their study programmes but not often directly addressed in national curriculum guidelines. The guideline documents of Estonia, Finland, and Sweden for compulsory basic education (children from 7 to 16 years old) are a case in point, and this article analyses how heritage is defined, in which contexts it appears, and what kind of effects it has in these educational policies. To accomplish this analysis, Critical Discourse Analysis is employed as a conceptual framework. It is argued that despite the claim made in the policies regarding heritage belonging to all, heritage is placed in opposition to history writing and associated with minority groups.